Women, Marriage and Property in Upper Canada: The Case of Elizabeth Sanders - Pétrin, Guylaine (Ontario History)

(untitled) (The Ontario Historical Society, 2013)
This article explores how one illiterate woman in Upper Canada, Elizabeth Sanders, used the few legal tools that were at her disposal to deal with a bad marriage and to protect her property for her daughters. Her social standing, her property and, even more importantly, the support of her family, allowed her to have access to and use the very deficient Upper Canadian justice system to deal successfully with a bad marriage. This study shows that even illiterate women could and did use the law to their advantage.